African son - Hemminger, William J. (University Press of America, 2012)
Records the author's many trips to Africa as a Peace Corps volunteer, Fulbright scholar, teacher, and traveler over four decades. These personal essays range from sympathetic descriptions of village life in Senegal and Cameroon to detailed accounts of the rich physical and natural worlds in Zimbabwe, Malawi, and Madagascar.